2006
DOI: 10.20882/adicciones.334
|View full text |Cite
|
Sign up to set email alerts
|

Estilos y representaciones de apego en consumidores de drogas

Abstract: El apego inseguro se ha revelado factor de riesgo de diversos problemas de salud mental. Parece plausible que el apego inseguro, en general desarrollado en la infancia, es un factor de riesgo de trastornos por consumo de drogas (TCDs), y esto podría también afectar la alianza terapéutica, y secundariamente, la evolución del TCD. Hemos revisado la literatura sobre este tema, buscando relaciones entre patrones de apego y TCDs. Los estudios publicados sobre apego y TCDs.han producido resultados poco consistentes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…This is valid both when attachment has been evaluated with the AAI (34, 39, 6873), self-reports (7489), and other interviews (90). A similar prevalence of the insecure models is also delineated by studies, which have exclusively focused on parents with drug use problems (9198). …”
Section: Attachment and Parenthood At Risk: Maternal Substance Addictionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is valid both when attachment has been evaluated with the AAI (34, 39, 6873), self-reports (7489), and other interviews (90). A similar prevalence of the insecure models is also delineated by studies, which have exclusively focused on parents with drug use problems (9198). …”
Section: Attachment and Parenthood At Risk: Maternal Substance Addictionmentioning
confidence: 78%
“…Although consistent research attests the prevalence of insecure attachment representations in adults with substance misuse, a specific association between drug-related disorders and a particular attachment style does not emerge (70, 98); indeed, some works have observed a prevalence of the anxious-preoccupied attachment style (73, 78, 81, 83, 99), while others have underlined the presence of the dismissing style (68, 71, 72, 77, 82, 90, 93). Others suggest an association with the unresolved loss and/or trauma (U) pattern (73, 92, 100).…”
Section: Attachment and Parenthood At Risk: Maternal Substance Addictionmentioning
confidence: 99%
“…The only review found on the relationship between attachment, as understood by the classic authors, and drug use in adolescence focused exclusively on the type of assessment instrument used, but without going into other methodological or conceptual issues (De Lucas Taracena & Montañes Rada, 2006). Except for this last work, the reviews included the topic of attachment but rarely as a central issue, merely noting that less attachment and lack of attachment are related to drug use.…”
Section: Resultsmentioning
confidence: 99%
“…2) The range of instruments used across the different studies evaluating attachment has contributed to the fact that the results obtained were not conclusive and generalizable (De Lucas Taracena & Montañes Rada, 2006). Thus, those studies that used questionnaires or interviews that permit the classification of attachment style as secure versus insecure (e.g., Hazan & Shaver's self-report questionnaire, HSSR; the Adult Attachment Interview, AAI; Bartholomew and Horowitz's semi-structured interview; the Collins and Read Inventory) indicate that, in general, drug use is linked to insecure attachment, of avoidant (Rosenstein & Horowitz, 1996), fearful (Schindler et al, 2007) or anxious type (Kassel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The primary strategy is the search for contact with the attachment figure (Pierrehumbert et al, 2002;Harnic et al, 2010). In relation to this idea, several studies conclude that substance dependence is related (a) to the ambivalent/ resistant type of insecure style of attachment, represented in Pierrehumbert's model by the dimensions "family concern" and "parental interference" (Pierrehumbert et al, 2002;De Lucas, & Montañés, 2006;Yuchang, Cuicui, Junxiu, & Junyi, 2017), and (b) to low parental concern or "parental permissiveness", as is expressed in this model, and "child trauma" (Miljkovitch et al, 2005). Drug users score low on secure attachment cognitions (Miljkovitch et al, 2005).…”
Section: Introductionmentioning
confidence: 92%